A systematic approach to critical multiculturalism and teacher education in EFL context: An integrative research review - Cansın Balcı (Literacy Trek, 2023)
Critical multicultural education (CME) challenges power imbalances in society and calls for the equitable distribution of power. It aims to address biases based on gender, class, and race, and improve social, economic, and educational opportunities for all individuals. While there have been several studies conducted on CME in relation to teachers and teacher training, there is a need to examine its broader implications for teacher education. This study aims to investigate the implications of CME on teacher education by analyzing different studies on this subject and their findings in various contexts. 14 relevant articles were compiled, categorized, and coded based on their context and findings, and descriptive data analysis was conducted. The study compared and contrasted the findings of the different studies and made generalizations about the implications of CME on teacher education and how it can be applied in the EFL context. The study highlights the importance of understanding the potential impact of CME on teacher education and provides insights for educators to effectively integrate CME principles into their teaching practices.